Uplink Cross-Layer Scheduling with Differential QoS Requirements in OFDMA Systems. (23rd September 2010) - Bai Bai, Bo Bo; Chen Chen, Wei Wei; Cao Cao, Zhigang Zhigang; Ben Letaief Ben Letaief, Khaled Khaled
Abstract : Fair and efficient scheduling is a key issue in cross-layer design for wireless communication systems, such as 3GPP LTE and WiMAX. However, few works have considered the multiaccess of the traffic with differential QoS requirements in wireless systems. In this paper, we will consider an OFDMA-based wireless system with four types of traffic associated with differential QoS requirements, namely, minimum reserved rate, maximum sustainable rate, maximum latency, and tolerant jitter. Given these QoS requirements, the traffic scheduling will be formulated into a cross-layer optimization problem, which is convex fortunately. By separating the power allocation through the waterfilling algorithm in each user, this problem will further reduce to a kind of continuous quadratic knapsack problem in the base station which yields low complexity. It is then demonstrated that the proposed cross-layer method cannot only guarantee the application layer QoS requirements, but also minimizes the integrated residual workload in the MAC layer. To further enhance the ability of QoS assurance in heavily loaded scenario, a call admission control scheme will also be proposed. The simulation results show that the QoS requirements for the four types of traffic are guaranteed effectively by the proposed algorithms.